EFL STUDENTS ENGAGEMENT IN SOCIAL NETWORK SITE- BASED LEARNING - Sri Yunita; Yustika Nur Fajriah; Susilawati Susilawati (Universitas Islam Nahdlatul Ulama Jepara, 2021)
Online learning is a choice to use in this current pedagogy. The most prominent power in online learning is the wide room for teachers to develop students engagement during the learning process. This study aims to figure out how students are engaged in online learning, to describe and examine in depth how they are engaging themselves in the online learning. This study employs a case study. The data were obtained from a collection of students chat and discussion in SNS. The data were obtained by observation, questionnaires and interviews. Observation data and questionnaires were analyzed by using Dixsons (2010, 2015) students engagement theory, which incorporates six engagement behaviors. As the analysis procedure, students chats and interview were analyzed inductively (Cresswell, 2012). The result shown that most of students were engaged in the online learning through the SNS application. Specifically, the engagement shown by the students to this simple application indicates that the impact of online learning on the students engagement is not determined by whether the platform used is high- or low.